The Twilight renaissance the role of visual imagery as a communication tool to maintain the popularity of the twilight films on twitter - Villanueva, Kristel Mae D. (2023)
This study looked into how the social media platform Twitter was utilized as an avenue of communication by two specific users to maintain the popularity of the Twilight Saga. The study aimed to answer which content types were the most popularly used, which content elements tended to gain the most engagement, and what aspects of Twitter were utilized to maintain engagement and interaction between members of the fandom. Guided by the created conceptual framework based on virality as a paradigm of digital communication and Julia Kristeva?s intertextuality, the study underwent a digital ethnographic qualitative research approach through netnography. Collected results from data gathering went through a thematic analysis and crossed reference with existing data through a systematic review. Through this research, it was found that images, along with familiar elements such as the films? main characters and external themes in popular culture were highly used and were found to be a popular among Twitter users which drove high engagement with content. The high engagement of the content made Twilight accessible to non-members of the fandom which increased its visibility and popularity, which supports the concept where fan clubs are a source of virality. The simple and open-source format of the Twitter platform also made it a favorable communication tool between users in and outside the fandom, with the fans like the subjects of this study being indirect ?ambassadors? who promote the Twilight brand.